Indigenous Malolactic Starter Cultures as Innovative Tools to Modify the Sensory Profile of a Wine: An Oenological Challenge - Elizabeth Naiquen Flores; Gabriel Alejandro Rivas; Andrea Cecilia Guillade; Natalia Soledad Brizuela; Marina Edith Navarro; Emma Elizabeth Tymczyszyn; Lucrecia Delfederico; Carolina Fabiana Perez; Liliana Carmen Semorile; Danay Valdes La Hens; Barbara Mercedes Bravo-Ferrada (Fermentation, 2025)
Malolactic fermentation conducted by lactic acid bacteria is essential for enhancing wine’s sensory qualities. Although this process can occur spontaneously through the action of native lactic acid bacteria (LAB) from the grapes and cellar, it carries risks such as increased volatile acidity, consumption of residual sugars, and the formation of undesirable metabolites like biogenic amines. This study evaluated the oenological potential of three innovative native malolactic fermentation starters (MLFS) on a pilot scale, aiming to offer local wineries cost-effective MLFS with native LAB strains. Alcoholic fermentation of Malbec grapes was carried out using a commercial yeast starter, followed by a sequential inoculation of native malolactic starters formulated with (i) mesophilic Lactiplantibacillus plantarum UNQLp11 and Oenococcus oeni UNQOe73.2, both from the Province of Río Negro; (ii) psychrotrophic Lentilactibacillus hilgardii UNQLh1.1 and Oenococcus oeni UNQOe19, both from the Province of Río Negro; (iii) mesophilic Lactiplantibacillus plantarum UNQLp1001, from the Province of Buenos Aires; and (iv) a commercial malolactic started, which served as a control. Malic acid was consumed by all starters. RAPD-PCR using M13 primer showed the native LAB’s capability for implantation in wine. A sensory analysis revealed distinct profiles for each formulation, despite having been inoculated at the end of the same alcoholic fermentation. These MLFS could replace imports, enhancing the region’s unique terroir.